2021
DOI: 10.1016/j.matt.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Humidity-Dependent Thermal Boundary Conductance Controls Heat Transport of Super-Insulating Nanofibrillar Foams

Abstract: We show that anisotropic foams based on aligned cellulose nanofibrils are superinsulating also at high relative humidity (RH). Thermal conductivity measurements and non-equilibrium molecular dynamic simulations show that the moistureinduced swelling and increase of the inter-fibrillar distance results in a reduction of the thermal boundary conductance that exceeds the thermal conductivity increase due to water uptake up to 75% RH. Phonon engineering by moisture could be used to tailor the heat transfer propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 53 publications
3
44
0
Order By: Relevance
“…This behavior has been attributed to two competing effects: the humidity-induced swelling of the fibrillar foam walls causes the thermal boundary conductance between particle surfaces to decrease as the distance between them increases; whereas at higher humidity, the replacement of air by water in the interparticle spaces increases the thermal boundary conductance. 5 Nevertheless, even at 80% RH, the λ r of AIT CNF-MC-TA was below the thermal conductivity of typical polystyrene foams (30–40 mW m –1 K –1 ). 42 The λ r of AIT CNF-MC-TA was slightly lower than that of an analogous foam prepared with only 60% as much TA (AIT CNF-MC-LTA ; Figure S9 ) for all values of RH, which suggests that addition of TA did not increase λ r .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…This behavior has been attributed to two competing effects: the humidity-induced swelling of the fibrillar foam walls causes the thermal boundary conductance between particle surfaces to decrease as the distance between them increases; whereas at higher humidity, the replacement of air by water in the interparticle spaces increases the thermal boundary conductance. 5 Nevertheless, even at 80% RH, the λ r of AIT CNF-MC-TA was below the thermal conductivity of typical polystyrene foams (30–40 mW m –1 K –1 ). 42 The λ r of AIT CNF-MC-TA was slightly lower than that of an analogous foam prepared with only 60% as much TA (AIT CNF-MC-LTA ; Figure S9 ) for all values of RH, which suggests that addition of TA did not increase λ r .…”
Section: Resultsmentioning
confidence: 94%
“…Further, moisture causes swelling in nanocellulose-based materials, increasing the distance between nanofibrils and thus phonon scattering and limiting thermal conductivity in aligned nanocellulose foams at moderate relative humidity. 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the wide range of applications of scaffolds produced by ice templating, a large number of research articles and reviews exist, [ 1–10 ] highlighting the increasing importance of this emerging process in recent years. Scaffolds with aligned porosity are highly interesting for various fields, from supercapacitors, [ 11–14 ] electrodes in batteries, [ 15,16 ] or thermal insulators [ 17,18 ] to biomaterials for tissue engineering, [ 19–22 ] 3D cell culture, [ 23 ] or as cell‐containing solid‐state scaffolds. [ 24 ]…”
Section: Introductionmentioning
confidence: 99%
“…(Solin et al 2020) Similarly, humidity-responsive chiral nematic CNC lms utilize the increase in the chiral nematic pitch of the helix with uptake of water to the change of color of the lm. (Chen et al 2020) Recently, it was also shown that moisture-induced swelling of CNM-based foams can also reduce the thermal conductivity due to enhanced phonon scattering (Apostolopoulou-Kalkavoura et al 2021).…”
Section: Introductionmentioning
confidence: 99%